Comparative study of secant, Fixed point and Sixth section methods for solving root in nonlinear equation / Nik Syahrul Naim Abdul Rahman - Abdul Rahman, Nik Syahrul Naim (2017)
Numerical analysis is to solve the functions for finding root by using a few numerical methods such as Secant, Fixed point and Sixth section methods to solve the functions for finding root. In this research, these methods are selected because it can be understand and has simple algorithm to use. The chosen methods are analyzed and compare it efficiency in order to solve the nonlinear function. The cubic polynomial, exponential, trigonometric, and logarithm functions are nonlinear function. For each nonlinear function, there are two difference functions were tested by using code Maple 17 software. The result is then analyzed based on the number of iterations and the central processing unit (CPU) times where it define the fastest calculation for the root. Even though, these methods are easy but it does possesses some errors compared to the exact root. So, it will produced error analysis. All three criteria are depends to a certain tolerance.